CTIM-03. PEMBROLIZUMAB MONOTHERAPY FOR MICROSATELLITE INSTABILITY-HIGH (MSI-H) OR MISMATCH REPAIR DEFICIENT (DMMR) RECURRENT GLIOMAS: RESULTS FROM THE MULTICOHORT PHASE 2 KEYNOTE-158 STUDY. (14th November 2022) - Baldini, Capucine; Cassier, Philippe A; Delord, Jean-Pierre; Simonelli, Matteo; Touat, Mehdi; Yao, Lili; Duic, J Paul; Gozman, Alexander; Marabelle, Aurelien
Abstract: BACKGROUND: Patients with recurrent glioma have limited treatment options. The anti‒ PD-1 monoclonal antibody pembrolizumab demonstrated antitumor activity as monotherapy in a subset of patients with PD-L1–positive recurrent glioblastoma (GBM) in the KEYNOTE-028 study; and durable clinical benefit in patients with previously treated unresectable/metastatic MSI-H/dMMR non-colorectal tumors in the multicohort KEYNOTE-158 (NCT02628067) study. We report outcomes with pembrolizumab in patients with MSI-H/dMMR recurrent glioma enrolled in KEYNOTE-158. METHODS: Adults with MSI-H/dMMR recurrent glioma, measurable disease per RECIST v1.1, ECOG PS 0/1, and tumor sample for biomarker analysis were eligible for cohort K (any MSI-H/dMMR advanced solid tumor, except colorectal cancer; local, prospective determination of MSI-H/dMMR status by PCR and/or IHC). Patients received pembrolizumab 200 mg Q3W for up to 35 cycles or until PD/unacceptable AEs (clinically stable patients could continue treatment until PD confirmed after ≥ 4 weeks). Primary endpoint was ORR per RECIST v1.1 by independent central review. RESULTS: Among 21 enrolled patients, all received prior temozolomide, 12 (57%) received prior bevacizumab, and 14 (67%) received ≥ 2 prior lines of therapy. 14 (67%) patients had GBM, 4 (19%) had oligodendroglioma/oligoastrocytoma, and 3 (14%) had glioma NOS. Median time from first dose to data cutoff (January 12, 2022): 50.0 months; 19 (90%) patients discontinued treatment. 1 patient with GBM had PR (ORR, 4.8% [95%CI, 0.1%‒23.8%]); duration of response was 18.9 months, PFS 29.2 months, and OS 32.7 months. 3 (14%) patients had SD; PFS was 23.2, 14.5, and 3.3 months; OS was 23.2, 15.1, and 9.1 months. Overall, median PFS and OS (95%CI) were 1.4 (1.0‒2.1) months and 5.6 (2.6‒16.2) months. Treatment-related AEs occurred in 7 (33%) patients (grade 3/4, n = 1; no grade 5) and led to discontinuation in 1 (5%) patient. CONCLUSIONS: Pembrolizumab demonstrated antitumor activity with manageable toxicity in a small subset of patients with relapsing/refractory MSI-H/dMMR glioma.